1982
DOI: 10.1071/pp9820155
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of the Polygalacturonases of Tomato Fruits

Abstract: Endopolygalacturonase [poly(1,4-α-D-galacturonide) glycanohydrolase, EC 3.2.1.15] was purified from ripening tomato fruits. The dominant enzyme in fruits at an early stage of ripening had a native molecular weight (Mr) of about 115 000, an isoelectric point (pI) of 8.6, and retained 50% of activity after 10 min at 70°C. Divalent metal ions enhanced the activity of this enzyme and ethylenediaminetetraacetate (EDTA) inhibited activity. In fully ripe fruits, two enzymes of Mr about 43 000 and 46 000 were most pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0
4

Year Published

1983
1983
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 0 publications
6
53
0
4
Order By: Relevance
“…Fruit pericarp tissue was homogenized with a Brinkmann Polytron in 3 vol of 1.3 M NaCl/0.05 M sodium phosphate, pH 6.0/40 mM 2-mercaptoethanol. The supernatant was recovered after centrifugation (11,000 x g, 30 min) and assayed for PG activity as described (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit pericarp tissue was homogenized with a Brinkmann Polytron in 3 vol of 1.3 M NaCl/0.05 M sodium phosphate, pH 6.0/40 mM 2-mercaptoethanol. The supernatant was recovered after centrifugation (11,000 x g, 30 min) and assayed for PG activity as described (6).…”
Section: Methodsmentioning
confidence: 99%
“…PG is involved in cell wall degradation and is the most extensively studied enzyme involved in ripening (6,7). Characterizations of PG cDNAs have indicated that the polypeptide has a molecular weight of S51,000, including a 71-amino acid N-terminal sequence which may be involved in export of PG to the cell wall (3,5).…”
mentioning
confidence: 99%
“…Although there is only a single gene for the catalytic PG polypeptide, the total PG activity isolated from ripe tomato fruit is attributable to a mixture of several closely related, post-translationally derived isoenzymes, PG1, PG2A, and PG2B (Pressey and Avants, 1973;Ali and Brady, 1982;Moshrefi and Luh, 1983;DellaPenna and Bennett, 1988). The PG2A and PG2B isoenzymes (herein referred to as the PG2 isoenzymes) accumulate late in the ripening process and are each composed of a single catalytic PG polypeptide differing only in the degree of glycosylation (Ali and Brady, 1982;DellaPenna and Bennett, 1988). The PG1 isoenzyme accumulates first during ripening and is thought to be composed of one or two catalytic PG2 polypeptides tightly associated with an ancillary glycoprotein, the p subunit protein (Moshrefi and To whom correspondences should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports focused on the physical properties of the enzyme including temperature of inactivation and specific ion interactions (3). These features of PG action have generally been evaluated using substrates, usually citrus pectin, of unspecified composition.…”
mentioning
confidence: 99%